Exploring Islamic Based Caring Practice in Intensive Care Unit: A Qualitative Study - Ismail, Suhartini; Hatthakit, Urai; Songwathana, Praneed (Department of Nursing, Faculty of Medicine, Diponegoro University, 2017)
Background: Even the advanced technology of modalities in intensive care unit (ICU) has been required a lot, it is important to date that nurses understand the Islamic faith-based healing in the holistic nursing care.Purpose: A phenomenological approach was conducted to describe the caring behaviors based on Islam for the patients in ICU from the perspective of nurses and patientsâ€™ family.Methods: Fourteen ICU nurses and 10 families participated in the study. In-depth interviews with nurses and families were conducted. The data were analyzed using inductive content analysis.Results: The findings revealed that Islamic-based caring in ICU was connecting to God (Allah), being present with patients and family, and nurses were an instrument to assist the patients and family to be faith in God. In addition, some barriers regarding Islamic based caring practice were presented, such as limited of knowledge and skill to provide Islamic based caring. Â Conclusion: Islamic based caring is very important in practicing the balance of body, mind, and spirit. It is suggested that the nurses are applying Islamic based caring improve the quality of care related to cultural care. The next investigation is needed to measure the nurse caring behavior based on Islamic perspective.